The Effect of Social Influence Mediated Intention to Use on Actual Usage of Mobile Banking - Putri Iskandar, Olivia; Puspitaloka Mahadewi, Erlina (Publisher Cv. Inara, 2025)
The increasing use of mobile banking indicates a change in people's behaviour in accessing financial services. However, not all users feel confident or comfortable continuing to use this service due to various personal and environmental considerations. This study aims to analyse the influence of Perceived Ease of Use, Perceived Usefulness, and Social Influence on Intention to Use, as well as the influence of Intention to Use on Actual Usage in the context of using mobile banking applications. This study uses a quantitative approach through a survey method by distributing questionnaires to 192 respondents, namely active users of BNI mobile banking services in the DKI Jakarta area. The analysis in this study was carried out using the SEM-PLS (Structural Equation Modelling - Partial Least Square) approach. From the data analysis, it was found that Perceived Ease of Use had a significant positive effect on Intention to Use, Social Influence had a significant positive effect on Intention to Use, while Perceived Usefulness had no significant effect on Intention to Use. In addition, Intention to Use had a significant positive effect on Actual Usage. This study provides very important implications for the development of bank digital service strategies, especially to increase the adoption of mobile banking among the younger generation.